USE OF JUDICIARY SYSTEM IN THE RIGHT OF THE PROTECTION OF PERSONAL DATA - Kāršenieks, Jānis (Administrative and Criminal Justice, 2018)
In the article the author analyzes the problems of protection of personal data of individuals in the judicial information system. In order to understand the essence of the problem, the author of the article analyzes the essence of the right to protection of personal data (data related to criminal offenses, criminal and administrative convictions) of individuals, the purpose of the judicial information system and the procedure and rules for using it of the given system.The scientific base of this research is the normative acts regulating both subjects of research, and judicial practice.This article addresses issues that have not previously been investigated. The article specifies the criteria, rules and principles that need to be considered and applied in practice with the judicial information system.